The Efficacy of Warm and Cold Compresses in Reducing Body Temperature among Hyperthermic Sepsis Patients - Lukito, Kurniawan Raharjo; Sahrudi, Sahrudi; Widiantari, Aninda Dinar; Murtiani, Farida (Universitas Pendidikan Indonesia, 2024)
Introduction: Clinical manifestations in sepsis patients include high fever (hyperthermia). Interventions to reduce fever can be done through non-pharmacological therapy, including cold and warm compresses. Objective: This study was determine the effectiveness of warm and cold compresses on temperature changes in hyperthermic patients in the ICU. Methods: This study was a quantitative study with a quasi-experimental pre-post design with a control group. The study was conducted at Sulianti Saroso Infectious Disease Hospital (SSIDH). The sample consisted of sixty (60) patients diagnosed with sepsis in the ICU, with thirty (30) patients receiving warm compress intervention and thirty (30) patients receiving cold compress intervention. The intervention involved a compressing procedure according to the hospital's SOP. Results: In the warm compress intervention group, the average body temperature before intervention was 38.740C; after intervention, it was 36.760C. In the cold compress intervention group, the body temperature before intervention was 38.590C; after intervention, it was 36.750C. There was a difference in body temperature before and after intervention for both warm and cold compresses (p-value=0.0001) but the changes in the two interventions were not statistically different (p-value=0.437). Conclusion: Both compresses are effective in reducing the body temperature of sepsis patients experiencing hyperthermia. The results of this study can be used as input for nursing interventions in ICU patients with hyperthermia problems with non-pharmacological interventions through warm compresses and cold compresses.